A tomographic TEM study of tension-compression asymmetry response of pyramidal dislocations in a deformed Zr-2.5Nb alloy. (August 2018) - Long, Fei; Kacher, Josh; Yao, Zhongwen; Daymond, Mark R.
Abstract: Plastic deformation induced pyramidal ⟨c + a⟩ dislocations in a Zr-2.5Nb alloy have been investigated by electron tomography in the transmission electron microscope. The 10 1 − 1 1st order pyramidal planes were determined to be the primary slip plane, with the 11 2 − 2 2nd order pyramidal planes acting as a secondary slip system. The slip behavior showed asymmetrical response with loading direction, characterized by restricted planar slip in ⟨c⟩ axis compressive loaded grains and frequent cross slip in ⟨c⟩ axis tensile loaded grains. Graphical abstract: Two of the observed ⟨c + a⟩ dislocations labeled as A and B were reconstructed in a 3D volume. Red and yellow color indicating segments lying on different planes which implying cross slip between two types of pyramidal planes.Unlabelled Image